The study on the relationship between the friction characteristic and the formability of the automotive steel sheet during the stamping process. Issue 1 (November 2020) - Kim, J Y; Yoon, S C; Hyun, J S; Lee, M.-G.
Abstract: This study aims to analyse the formability characteristics by friction characteristics of automotive steel sheets to improve sheet forming during the stamping process. During the stamping operation, the steel sheet is pushed into the tool surface, a complex phenomenon occurs, and many parameters interact. Therefore, automotive steel researchers want to optimize the friction of automotive steel sheets to improve the forming process, such as drawing ratio limit, dome height limit, cup drawing test, etc. In addition, in this study, the finite element method is used in combination with a numerical solution to present the friction behavior of high strength steel sheets in automobiles, taking into account the operating deformation mechanism during the formability test.